2022
DOI: 10.1177/02692163221138880
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative service evaluation of patient and caregiver experiences of CAR-T therapy: Recommendations for service development and implications for palliative care teams

Abstract: Background: Chimeric Antigen-Receptor-T-cell (CAR-T) therapy is a potentially life-saving treatment for refractory haematological malignancies. Internationally, CAR-T services are undergoing rapid development. Despite this, research on the lived experiences of patients receiving novel immunotherapies is limited. Little is known about their supportive care needs. Consequently, dedicated palliative and supportive care services may not be considered. Aim: To explore the patient and caregiver experience of CAR-T t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Moreover, these constructs are important mitigators of uncertainty-related distress, a source of emotional distress common not only to our pediatric cohort, but another study among adult patients treated with CAR T cell therapy. 21,35 Thus, supporting hope, trust, and self-efficacy are likely important in providing quality supportive care for families during CAR T cell therapy. General psychosocial challenges, though not unique to CAR T cell therapy, were also commonly endorsed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these constructs are important mitigators of uncertainty-related distress, a source of emotional distress common not only to our pediatric cohort, but another study among adult patients treated with CAR T cell therapy. 21,35 Thus, supporting hope, trust, and self-efficacy are likely important in providing quality supportive care for families during CAR T cell therapy. General psychosocial challenges, though not unique to CAR T cell therapy, were also commonly endorsed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those of Cheng et al [ 24 ], who conducted a focus group with 18 adult patients who were further from their CAR-T therapy (6 months to 2.5 years) than our patients (2 weeks to 6 months) but nevertheless described impairments in social, emotional, and physical functioning following CAR-T therapy, with participation in social roles and activities the concept most frequently mentioned in both samples [ 24 ]. A qualitative interview study of 10 patients and 4 caregivers identified 3 themes associated with the CAR-T therapy experience: (1) communication with healthcare professionals, (2) social isolation, and (3) wide variation in treatment toxicities, with common side effects including fever, fatigue, reduced appetite, and memory/cognition problems [ 25 ], each of which was a key theme in our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…41,44,[104][105][106] Patients undergoing CAR-T cell therapy may experience a sense of loss, isolation, and frustration during repeated cycles of treatment and relapse, along with fear of recurrence and difficulty planning for the future in face of the uncertain prognosis following CAR-T cell therapy. 107 Additional challenges include the financial burden associated with treatment as well as the geographic, socioeconomic, and racial barriers to accessing CAR-T cell therapy. 41,105,108 Many patients also experience a short-term decline in quality of life during the first 2 weeks after infusion, coinciding with the period of hospitalization and peak symptom burden, while lingering fatigue, drowsiness, and reduced appetite are also common during the first 3 months.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…Qualitative research studies have revealed a significant burden of psychologic distress among CAR‐T cell recipients, including frequent symptoms of anxiety, depression, and post‐traumatic stress disorder 41,44,104–106 . Patients undergoing CAR‐T cell therapy may experience a sense of loss, isolation, and frustration during repeated cycles of treatment and relapse, along with fear of recurrence and difficulty planning for the future in face of the uncertain prognosis following CAR‐T cell therapy 107 . Additional challenges include the financial burden associated with treatment as well as the geographic, socioeconomic, and racial barriers to accessing CAR‐T cell therapy 41,105,108 .…”
Section: Psychosocial Effectsmentioning
confidence: 99%